PENGEMBANGAN KURIKULUM PTAI YANG TERKAIT DAN SEPADAN DENGAN KURIKULUM MADRASAH - Syafruddin Nurdin (AT-TA'LIM, 2013)
One of the most important agendas of the current education is to link and match between curriculum across educational level and the job together with stakeholders.  To link and match the curriculum of inter education level, it is necessary to understand the vision and mission, the institutional goal, the curriculum and its characteristics.  Besides, it is also important to apply the general principles of curriculum development namely relevance, continuity, and integrated.  Process of curriculum development is of the following steps: (1) identifying the determinant factors in the curriculum development and conducting Need Assessment; (2) identifying the competence or profile of the outputs; (3) identifying knowledge, attitudes, and skills that are necessary for the required competence; (4) arranging the Structure of Curriculum Program, and (5) developing syllabus. Copyright © 2013 by Al-Ta'lim All right reservedDOI: 10.15548/jt.v20i2.33